Sugar furanoid trans-vicinal diacid as a gamma-turn inducer: synthesis and conformational study - Vangala, Madhuri; Dhokale, Snehal A.; Gawade, Rupesh L.; Pattuparambil, Rajamohanan R.; Puranik, Vedavati G.; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2013)
A simple method for the synthesis of a sugar furanoid trans vicinal diacid and its incorporation into the N-terminal tetrapeptide sequence (H-Phe-Trp-Lys-Thr-OH) to get glycopeptide 8 has been described. 2D NMR and MD simulation studies of 8 clearly show that the sugar diacid adopts a gamma-turn conformation towards the N-terminus.